A Linguistic Study of Ted Hughes’ Language and Style - Izzat Salman, Anees; Abdul- Jabber Khadum, Basima; Hameed Aubdlatif, Hussein (Opción, 2019)
The study attempts to check the language and the style of Ted Hughes in his poem The Warm and The Cold. The poem is around the weather and how this weather affects all living creatures especially when it is cold; i.e., the poet Hughes shows how the natural world copes with extreme weather conditions. While the animals seem to be well-adapted and ’warm’ despite the ’cold’. The study is going to adopt an approach of language and stylistics of Short (1996) for the purposes of linguistic analysis. The study tends to point out and analyze the subsequent levels: lexical, grammatical and phonological with reference to the concept of foregrounding. The study aims to show how the stylistic approaches are benefit for the readers to understand the literary piece in a better way. The findings and discussion of study present how Hughes uses these stylistic or linguistic devices to show to what extent the animals, insects, fishes and birds endure the harshness of weather.